Duplikasi Lambung Yang Dikelola Dengan Mucosektomi Dan Perbaikan Lambung: Laporan Kasus Yang Langka - Aslam, Filza RA; Ismar , Ibrahim; Wahid, Tubagus OR; Valentino, Andrea; Salamullah, Salamullah; Sabrina, Viona (Universitas Kristen Maranatha, 2025)
This case report aims to present the clinical presentation, diagnostic workup, surgical management, and outcome of a rare case of gastric duplication in an infant. Gastrointestinal duplication (GD) is a rare congenital anomaly accounting for 4–8% of all duplication cases, predominantly occurring in children. An 8-month-old female presented with a progressively enlarging abdominal mass, vomiting, and distension. Initial ultrasound months earlier showed a mass near the umbilicus, but the family pursued alternative treatments. Examination revealed a well-defined, rubbery cystic mass (8 × 5 cm). Sonography showed a septated cystic lesion, and a barium study demonstrated a filling defect. The patient underwent exploratory surgery with mucosectomy and gastric repair. Postoperatively, she received intravenous fluids, antibiotics, analgesics, and proton pump inhibitors. Despite transient vomiting and distension, by day seven, she gained weight and was discharged. Histopathology confirmed a benign gastric duplication cyst. At 11-day follow-up, she was thriving and feeding well. This case underscores the importance of early diagnosis and surgical intervention in GD to prevent complications and highlights favorable outcomes with timely management.